STUDY ON MAKING TYROSINASE BIOSENSOR FROM ASPERGILLUS ORYZAE TP01 AND ITS APPLICATION - Hằng, Trịnh Thu; Sâm, Nguyễn Thị Xuân; Huyền, Đỗ Thị Thu; Thu, Đặng Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY Tyrosinase (EC 1.14.18.1) is a Polyphenol oxidase. It is a bifunctional enzyme catalyzing the monohydroxylation of monophenols and the oxidation of diphenols. Tyrosinase is used to medicine, food industry and environmental protection, especially used to create the biosensor. Tyrosinase has been purified by Mono Q HR 5/5 column in FPLC system with the result of 18.96 folds as the rude enzym, its specific activity is 204.75 U/mgPr and its yield is 31.63%. Determining the optimum condition to immobilised the enzym on biosensor: the amout of tyrosinase is 50U, duration of 30 minutes, BSA of 1.3mg in saturated glutaraldehyt, reutilization of 12 times. After 50 days the biosensor is preserved in the tinned bag at 4oC, the output signal remains 79.51%. The optimum condition of the biosensor is the temperature of 30oC, pH 6.6, subtrate density of 10-7 – 4 × 10-4 M. Biosensor has been detected monophenol compound from the density of 10-7 M–3 × 10-4 M and diphenol compound from 10-6 M – 4 × 10-4 M. Application of tyrosinase biosensor has been detected atrazin, diuron, 2.4D and phenol compounds in waste water from the petrolium, chemical, tobacco, dying and soaping factories.